As representações cristãs do mal e do Diabo em "De casu diaboli" de Anselmo de Bec (séc XI) - Carniel, Joana Scherrer (2022)
In the current essay we study the treatise De casu diaboli, written by Anselm of Bec during the years of 1085-1090, while he held the office of abbot at the Benedictine monastery located at Bec, in Normandy (present-day France). In the treatise, Anselm discusses some matters that to this day provoke discussions in Christian theodicy, among them the main one is: if God is supreme good and supreme essence and from him only what is good and essence is derived, what is evil and where does it come from? Firmly based on the authority of Augustine of Hippo, Anselm assumes that there is no ontology in evil, understanding it as deprivation or lack of good (privatio boni). Therefore, what exists is moral evil, understood as sin. In this context, the abbot — always writing in accordance with Christian tradition — introduces the figure of the devil as a device to explain the existence of evil without making God responsible for it. This observation leads to the second problem: why did lucifer sin? In his answer, he argues that the evil angel abandoned the justice in which he was created from the moment he wanted what he should not and could not want. And what did he want? Happiness in a disorderly manner. By wanting what he could not, lucifer acted in his own will, not subjected to anyone, something inconceivable for a being that owed its existence to a creator. That said, his sin was disobedience. The main challenge posed to this research was to approach a document with theological-philosophical content from the historical point of view. Thus, it was guided by the following question: why did the abbot of Bec propose to lecture about evil and lucifer in the context of the 11th century? For this, we analyze the work from the perspective that it was part of a pedagogical project by Anselmo, which aimed to bring the devil as a bad example, in order to educate his monks in a moral standard of Christian conduct. For this examination of Anselm's work, we use Michel Foucault's concepts of pastoral power (2008), Roger Chartier's representations (2002) and the methodological propositions of Laurence Bardin's Content Analysis (2011).